Adaptation Test Of Sweet Potato (Ipomoea batatas L. (LAM)) Cilembu Variety In South Sumatra - Faridatul Mukminah; Zulkarnain Husny; Miftahul Ma'ruf (Jurnal Agroekoteknologi, 2022)
Adaptation Test of Sweet Potato (lpomoea batatas L. (Lam)) variety Cilembu in Ogan Ilir, South Sumatra was conducted to see if sweet potato var. Cilembu was planted in Ogan llir area is be able to form tubers and has a higher sugar content compared to local varieties in Ogan Ilir South Sumatra. This research was carried out in the Agroteknopark area located in the village Bakung, North Indralaya, Ogan Ilir, on April 2017 to September 2017. This study used a Randomized Block Design, consisting of four clones and six replications. To find out the differences in each variety, group comparison tests were carried out using the orthogonal contrast method. From the results of the study it can be concluded that the highest plant lenght of the local variety were obtained from the Purple variety. The highest plant length of Cilembu variety obtained from the Rancing variety. The highest diameter of tubers of Local variety plant was obtained from Orange variety 9.8 cm, while the highest diameter of Cilembu variety was 5.9 cm (Rancing variety). The highest weight of tubers from local varieties were obtained from Orange variety, namely 1.39 kg plant-1 or 34.79 tons ha-1. The highest  Cilembu varieties obtained from Rancing variety were 1.2 kg plant-1 or 21.67 tons ha-1, the highest weight of biomass per plant at the highest L vs C ratio was obtained from the Cilembu Rancing variety of 4.9 kg. On parameter of dry biomass weight, the higher L vs C ratio was obtained from the Cilembu Rancing variety which was 0.73 kg.